Effectiveness of Family Health Strategy on child's health indicators in São Paulo State - Venancio,Sonia Isoyama (2016)
Abstract Objectives: to evaluate the effectiveness of Family Health Strategy (FHS) on child's health indicators in São Paulo State. Methods: longitudinal ecological study involving all the towns in São Paulo State from 1998 to 2009. The outcomes were the coefficients of infant mortality and its components and the rate for pneumonia and diarrhea hospitalizations. The main independent variable was "FHS coverage"; the covariates considered the context of sociodemographic and the health system. Negative binomial regression models of fixed effects and STRATA 11.1 statistical program were used. Results: FHS coverage above 50% showed a protective effect in relation to the postneonatal mortality (RR: 0.93; CI 95%: 0.87-1.00) and coverage up to 50% (RR 0.88 CI95% 0.82-0.99) or above 50% (RR: 0.87; CI95%: 0.82-0.92) were protective factors for pneumonia hospitalizations. Conclusions: the effectiveness of FHS on the outcomes related to child's health may vary according to local and regional contexts.